Anatomical Septal Variations in the Maxillary Sinus and Associated Pathological Findings: A Retrospective Cone-Beam Computed Tomography Study - Rayan M. Meer; Ahmed M. Kabli; Rawan K. Kamal; Albraa B. Alolayan; Mohamed Omar Elboraey (Journal of Clinical Medicine, 2026)
Background/Objectives: Detailed study of the anatomy of the maxillary sinuses is crucial for reducing the risk of complications in sinus augmentation and implant procedures, endodontic surgical treatment, and other operations in the posterior maxilla. This retrospective cone-beam computed tomography (CBCT) study aimed to investigate maxillary sinus volume, septal morphology and distribution, ostium height, and pathological findings, as well as their interrelationships, in a Saudi clinical cohort using combined three-dimensional volumetric and morphometric analyses. Methods: A retrospective analysis was performed on 360 CBCT scans obtained from patients after applying predefined inclusion and exclusion criteria. The volumes of the maxillary sinuses were measured by means of semi-automatic segmentation with ITK-SNAP software, while the structure of the septum, anatomical position, orientation, and internal architecture were assessed with BlueSky Bio software. The vertical distance from the natural opening to the bottom of the sinus and pathologies of the Schneiderian membrane were also studied. Results: The mean volume of the left maxillary sinus was found to be larger than the right (14,948.6 ± 5473.5 and 13,937.6 ± 4020.7 mm3, respectively). No sexual differences were noted with regard to sinus sizes. The prevalence of septa was 80.3% for the left side and 77.5% for the right side. The septa were mostly incomplete, with complete septa being less common. Various types of positioning and orientation were recorded for the septa, with a peak in the molar region. In the case of the left sinus, the height of the ostium was greater in men than women (p = 0.007); no differences were observed for the right side. Conclusions: The anatomy of the maxillary sinus shows great three-dimensional variation in terms of the shape of septa, the volume of the sinus, the height of the ostium, and any pathological changes related to that anatomy. The significant relationship between the presence of septa and the pathology of the mucosa highlights the need for adequate preoperative CBCT analysis of the anatomy.